Residues investigation of fluoroquinolones and sulphonamides and their metabolites in bovine milk by quantification and confirmation using ultra-performance liquid chromatography–tandem mass spectrometry. (1st May 2015) - Meng, Zhe; Shi, Zhihong; Liang, Shuxuan; Dong, Xinfeng; Li, Hui; Sun, Hanwen
Highlights: An UPLC–MS/MS method for multiclass and multiresidue analysis is developed. Fragmentation pathway of fluoroquinolones, sulphonamides and metabolites was presented. The quantification limits of the 17 analytes were well below the MRLs. The method can ensure quantification analysis of bovine milk at low μg kg −1 level. Abstract: A novel UPLC–MS/MS method for quantification and confirmation of eight fluoroquinolones, five sulphonamides (SAs) and four acetyled metabolites in milk is developed. Their main fragmentation pathways were presented. The limits of quantification were in the range of 0.01–0.29 μg kg −1 for FQs and 0.13–1.68 μg kg −1 for SAs. Mean recoveries ranging from 61% to 115% were achieved at spiked level of 0.5–100 μg kg −1 . The intra- and inter-day precisions were in the range of 6.3–10.7% and 9.0–13.4%, respectively. This novel approach has high speed and sensitivity, and can ensure the multiclass and multiresidue analysis of bovine milk at low μg kg −1 level. The content of each analyte residue is much lower than the maximum residue limits. Some residues in milk were confirmed in according to the Commission Decision 657/2002/EC.